Students' Perceptions of the Internalization of Islamic Values in Buffer Solution Teaching Materials - Uun Sundari; Leny Heliawati*; Anna Permanasari (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
Learning that has a divine value has an important role in preparing a generation of higher quality, who masters science and technology with good morals. This study aims to analyze students' perceptions of chemistry teaching materials on buffer solution material with Islamic internalization values. This study compares students' perceptions of teaching materials that have been used with teaching materials internalized with Islamic values. The perception of the Islamic value in this study was measured by analyzing the motivation, use, and belief of the buffer solution teaching material that integrates Islamic values. This type of research is ex post facto research by collecting data directly to respondents through questionnaires, interviews, and observations. The data analysis technique was done by descriptive qualitative method. This research conducted on 50 eleventh dan twelfth-grade students. The target analysis of these needs is focused on students studying in Islamic-based schools. The results showed that the number of students in the category of “highly need teaching materials with Islamic internalization” was 36 people (72%), 14 people are in “need” category (28%), and no one was of the view that teaching materials with Islamic internalization were not needed. From this study, we can conclude that students in Islamic-based schools have good perceptions and need buffer solution teaching material with Islamic internalization values